Antidepressant effects of Crocus sativus stigma extracts and its constituents, crocin and safranal, in mice - H Hosseinzadeh; Gh Karimi; M Niapoor (Institue of Medicinal Plants, ACECR, 2004)
As in traditional medicine, saffron is used as exhilarating agent and also our previous study showed the antidepressant effect of saffron extracts, in this study, the effects of aqueous and ethanolic extracts of Crocus sativus stigma and its constituents safranal and crocin were studied for the antidepressant activity using the forced swimming test in mice. The extracts and constituents were injected intraperitoneally to mice. The aqueous (160-320 mg/kg) and ethanolic extracts (200-800 mg/kg) of stigma decreased the immobility time in comparison to normal saline and also like fluoxetine increased the swimming time. In the open field activity test, the aqueous extract reduced total activity but the ethanolic extract increased the stereotypic activity. Safranal and crocin also reduced the immobility time. Safranal increased the swimming time. Both safranal and crocin increased the climbing time. Crocin increased stereotypic activity and safranal decreased the total activity. On the basis of these results, the antidepressant effect of Crocus sativus stigma extracts may be mediated via safranal and crocin. Crocin may act via the uptake inhibition of dopamine and norepinephrine and safranal via the serotonin. Further experiments are needed to clarify these subjects.